Comparative profiling of miRNA expression in developing seeds of high linoleic and high oleic safflower (Carthamus tinctorius L.) plants - Cao, Shijiang; Zhu, Qiao-Hao; Shen, Wanxia; Jiao, Xiaoming; Zhao, Xiaochun; Wang, Ming-Bo; Liu, Lixia; Singh, Surinder; Liu, Qing (Frontiers in Plant Science, 2013)
Vegetable oils high in oleic acid are considered to be advantageous because of their better nutritional value and potential industrial applications. The oleic acid content in the classic safflower oil is normally 10-15% while a natural mutant (ol) accumulates elevated oleic acid up to 70% in seed oil. As a part of our investigation into the molecular features of the high oleic (HO) trait in safflower we have profiled the microRNA (miRNA) populations in developing safflower seeds expressing the ol allele in comparison to the wild type high linoleic (HL) safflower using deep sequencing technology. The small RNA populations of the mid-maturity developing embryos of homozygous ol HO and wild type HL safflower had a very similar size distribution pattern, however, only ~16.5% of the unique small RNAs were overlapping in these two genotypes. From these two small RNA populations we have found 55 known miRNAs and identified two candidate novel miRNA families to be likely unique to the developing safflower seeds. Target genes with conserved as well as novel functions were predicted for the conserved miRNAs. We have also identified 13 miRNAs differentially expressed between the HO and HL safflower genotypes. The results may lay a foundation for unravelling the miRNA-mediated molecular processes that regulate oleic acid accumulation in the HO safflower mutant and developmental processes in safflower embryos in general.